Diastolic Mitral Regurgitation Caused by Acute Myocardial Infarction Complicated With Severe Heart Failure - Wataru Suzuki; Kentaro Mukai; Hirofumi Ohashi; Yoshiyuki Ogawa; Manami Ono; Masanobu Fujimoto; Hirohiko Ando; Tetsuya Amano (Annals of Internal Medicine: Clinical Cases)
Diastolic mitral regurgitation (MR) is a rare and often-overlooked form of functional MR. Key factors in the development of diastolic MR include incomplete closure of the mitral valve, reversal of left atrioventricular pressure gradient during diastole, and elevated left ventricular diastolic pressure. In this case, diastolic MR was observed in an older male patient with a single underlying pathologic condition, acute myocardial infarction. Remarkably, the diastolic MR resolved after treatment of myocardial infarction. This case highlights the importance of understanding the complex hemodynamic changes involved.